Prognostic nomogram for resected pancreatic adenocarcinoma: a TRIPOD-Compliant retrospective long-term survival analysis - Xu, Dong; Neoptolemos, John P. (World journal of surgery, 2020)
Prognostic prediction had been widely used in various cancer entities, from early screening to end-stage patient caring. Currently, there is hardly any well-validated nomogram which exists for long-term survival prediction in pancreatic adenocarcinoma (PC) patients in a post-surgery setting. Our objectives are to identify possible prognostic factors in PC patients following radical resection and to develop a prognostic nomogram based on independent survival predictors.